Three-Dimensional 3D/Ni Fe – GPL Coating of Microextraction Fiber for Determination of Polycyclic Aromatic Hydrocarbons - Marzieh Piryaei; Mir Mehdi Abolghasemi; Omid Rangouri Basmenj (Nanochemistry Research, 2025)
In the subsequent phase of this study, a 3D/Ni Fe – GPL fiber was created using the hydrothermal technique and analyzed using SEM, EDX, and mapping methods. Its capability to extract polycyclic aromatic hydrocarbons from river water samples was then assessed using the HS-SPME technique. The findings indicated that the synthesized fiber was suitable for quantitative analysis. The desorbed analytes were identified via GC-MS after being extracted from the fiber's surface. Under ideal conditions, a linear response for these substances was noted, spanning from 0.0001 to 100 µg L−1, with correlation coefficients (R2) between 0.993 and 0.999, and detection limits (LOD) ranging from 0.4 to 0.9 ngL−1. This newly developed fiber was effectively applied in the analysis of agricultural pesticides in fortified river water samples, yielding RSD% values from 2.3% to 8.2%. According to the obtained data, it can be said that this fiber has a good ability to extract and identify PAH by the microextraction method.